Number of coils necessary to treat cerebral aneurysms according to each size group: a study based on a series of 952 embolized aneurysms - José Ricardo Vanzin; Daniel Giansante Abud; Marco Tulio Salles Rezende; Jacques Moret (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: The Brazilian public health system determines a quantity of coils allowed to treat a cerebral aneurysm. The goal of this paper was to determine the number of coils necessary to treat an aneurysm based on size. METHODS: All patients harboring an aneurysm treated by endovascular approach between 1999 and 2003 were reviewed. RESULTS: There were 952 aneurysms included. Mean diameter sac was 8.2 mm with 7.9 coils per aneurysm. Out of 462 small aneurysms, mean size was 4.8 mm, with 4.6 coils/aneurysm used. A total of 315 medium aneurysms were treated, mean size was 8.6 mm, with 8.2 coils. Out of 135 large, mean size was 17 mm, with 16.1 coils. Forty giant aneurysms were treated with a mean size of 32 mm and 28.7 coils. CONCLUSIONS: We propose size as a reference to predict the number of coils necessary to treat each aneurysm: one coil for each millimeter of diameter.